The Important Dimension of the Methodological Language Learning Model - Šernas, Vytautas (Acta Paedagogica Vilnensia, 2006)
The object of the article – methodological cultural dimension of language learning. There are briefly observed other models as well (acculturation, nativization, denativization) which are related to a country’s strategy and tactics of the cultural development. On the basis of the research there are revealed relations of the culture and language indicated the main areas: spiritual culture: literature, music, art, architecture, etc.; a country's realia: habits, traditions, folk songs, humour, etc.; a country's geography, history; material civilization; culture-bound language phenomena (specific lexis, etc.). The article reveals the purpose of the methodological theoretical model of language learning: to ensure pure multilingualism in the process of implementation. It also deals with the differentiated interaction of cultures of the countries speaking Lm, L1, L2 languages taking place in a person's psyche. The article highlights the interaction of mother and foreign countries' cultures, there are given examples. At the end of the article there are enumerated some burning issues: 1) the development of system of original textbooks for each foreign language with the reference not only to the linguistic but to the cultural dimension as well; 2) the improved language teachers training; their retraining; 3) the expanded research of the cultural dimension; 4) the expanded metacognitive research of autonomous language learning, as the process of language learning is superindividual.
Keywords: cultural dimension; cultural education; multilingualism; language learning